2020
DOI: 10.6001/chemija.v31i1.4169
|View full text |Cite
|
Sign up to set email alerts
|

Sol–gel synthesis of calcium phosphate-based coatings – A review

Abstract: Calcium phosphate (CP)-based biomaterials, especially nanostructured ones, show a high biocompatibility and increased biological properties. The coatings composed of stoichiometric hydroxyapatite have been extensively used to improve integration of metallic implants in the host bone. However, these coatings exhibited several drawbacks that limited their successful application. It was concluded in numerous articles that the sol–gel derived coatings can undergo cracking and delamination and are scarcely uniform.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…[ 90 ] In addition to the above advantages of HA‐coated via the dip coating method on the metallic substrate, Tian et al showed that the adhesion of HA coating with Ag substitution could reduce the Staphylococcus epidermidis and Staphylococcus aureus bacteria on the substrate surface in in vitro study. [ 88 ]…”
Section: Different Methods Of Pin Coatingmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 90 ] In addition to the above advantages of HA‐coated via the dip coating method on the metallic substrate, Tian et al showed that the adhesion of HA coating with Ag substitution could reduce the Staphylococcus epidermidis and Staphylococcus aureus bacteria on the substrate surface in in vitro study. [ 88 ]…”
Section: Different Methods Of Pin Coatingmentioning
confidence: 99%
“…[87] Accordingly, the quality of the coated layer in the coating method depends on the speed of withdrawal, the sintering process after covering the layer, and suspension concentration. [88] Harun et al showed that coating HA on metallic substrates improves the corrosion resistance of the biomaterials due to increase substrate adhesion. [86] In the following, Nikbakht et al confirmed that the coated implant surface would induce toxicity on the surface of the pin due to impeding cells by raising the pH value of the dipping solution.…”
Section: Dip Coatingmentioning
confidence: 99%
“…For the preparation of CaP coatings on alloy surfaces, various physical deposition methods have been used, such as thermal spraying, matrix-assisted pulsed laser evaporation, magnetron sputtering, etc. Generally, these physical deposition methods often require harsh process conditions [25]. For example, atmospheric plasma spraying involves injecting calcium phosphate powder into a plasma jet, which operates at extremely high temperatures in the range of ten thousand degrees.…”
Section: Introductionmentioning
confidence: 99%
“…Such high temperatures can cause incongruent melting of calcium phosphate particles, leading to structural modifications, uncontrolled phase changes, and chemical decomposition [26][27][28]. Wet chemical methods, such as sol-gel, micro-arc oxidation, electrochemical deposition, etc., have been engaged to prepare CaP coatings due to the advantages of short coating formation times, applicability to irregular metal surfaces, low cost, and reduced environmental impact [25,29].…”
Section: Introductionmentioning
confidence: 99%
“…Sputtering is the technique of choice for magnesium [25][26][27] due to the high adhesion strength and uniformity of the coating produced [28,29]. Other coating techniques possess limitations with nonuniformity on complex geometries [22,30], poor adherence [31] and cracking [32] which could potentially drive corrosion. Calcium phosphate (CaP) thin films sputtered using hydroxyapatite (HA) targets are among the most investigated sputter coating application for magnesium substrates [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%